Openness of the Croatian economy in the context of monetary and fiscal policy - Samodol, Ante (Oeconomica Jadertina, 2022)
This paper examines the impact of selected monetary and fiscal variables on the trade openness of the Croatian economy. The openness of the economy is in theory considered one of the factors of economic growth. Given that monetary and fiscal policy are key components of economic policy, this paper examines the impact of monetary and fiscal variables on the level of openness of the economy. Monetary variables include money supply, exchange rate and inflation while fiscal variables include the share of budget revenues and expenditures in GDP and interest on the Ministry of Finance Treasury bills. Trade openness as an endogenous variable is defined by the share of the collective exports and imports in GDP as total openness, and the share of the individual exports and imports in GDP as export and import openness. Three models of multiple linear regression analysis have shown that significant fiscal variables, as opposed to monetary ones, dominated in determining the direction and magnitude of openness. One monetary variable is significant only in the case of import openness. As a secondary goal, the paper also analysed the impact of trade openness on economic growth through GDP per capita, which proved to be insignificant for economic growth of Croatia.